Evaluasi Risiko Rantai Pasok pada Komoditas Bawang Merah di Lampung - Rizqa Ula Fahadha; Tutik Nuryati; Sutarto Sutarto (OPSI, 2019)
The Study of supply chain risk in shallot commodity needs to take more concern. This is related to the increasing number of risks that faced in different the Industrial and business world. Based on these risks, currently the condition of the Shallot commodity supply chain performance is less than expected. In Relations of existence of risks in the supply chain, risk management plays an important role in keeping the supply chain system in order to be not disrupted. Risk Management is the part. Risk management is an integral part of the management process that runs continuously to minimize losses either increase opportunities or opportunities. This risk management process starts from the process of risk identification, risk assessment, mitigation, monitoring and evaluation. The purpose of this research is to evaluate the risk of supply chain shallot commodity. The Step that has to do is risk identification, risk analyze, and risk evaluation of supply chain. House of Risk (HOR) model is the method that used to identification, analyze, and evaluation the risk of shallot commodity.